Innate immune activation and depressive and anxious symptoms across the peripartum: An exploratory study. (January 2019) - Osborne, Lauren M.; Yenokyan, Gayane; Fei, Kezhen; Kraus, Thomas; Moran, Thomas; Monk, Catherine; Sperling, Rhoda
Highlights: Recent evidence indicates complex associations between immune functioning and depression. Perinatal evidence is sparse, and rarely includes anxiety, which is more prevalent than depression in pregnancy. This study measured mood, anxiety, and 23 cytokines at 5 points in pregnancy and postpartum in 51 women. We found increased pro-inflammatory markers across the peripartum for subjects with more depressive and anxious symptoms. Results indicate increased activation of the innate immune response in late pregnancy in psychiatrically ill women. Abstract: Background: There are complex associations between immune function and mental illness, yet studies in the perinatal period focus primarily on individual inflammatory markers and depressive symptoms only, cross-sectionally. We sought to examine associations between both depressive and anxious symptoms and immune activation longitudinally across the peripartum. Methods: We measured mood (Beck Depression Inventory, BDI-1 A) and anxiety (State-Trait Anxiety Inventory, STATE) and levels of 23 cytokines at 5 points in pregnancy and postpartum in 51 women. Within subject cytokine trajectories over time by depressive and anxious symptom grouping were assessed using linear mixed effects models with random intercept and slope. We also undertook an exploratory cluster analysis based on third trimester cytokine values. Results: Based on categorical BDI scores, IL-6 ( p  <  0.001), IL-15 ( p  =  0.047), GCSF ( p = 0.003), and CCL3 ( p < .001) were significantly different across time, with IL-6 ( p  <  0.001), IL-15 ( p  =  0.003), and CCL3 ( p  <  0.001) higher at the third trimester visit in more depressed subjects. Based on categorical STATE scores, GM-CSF significantly decreased across pregnancy for the less anxious group ( p  = 0.016), but not for the more anxious, and CCL3 ( p = 0.017), CXCL8 ( p = 0.011), and IL-6 ( p < 0.001) were higher at the third trimester visit for more anxious subjects. In exploratory cluster analysis based on cytokine level, there were no differences in mood or anxiety scores, but significant differences by race/ethnicity and overweight/obesity status. Women with higher pro-inflammatory cytokine values are more likely to be Hispanics (69.2% vs. 21.4%, p  =  0.015), but less likely to be African American (23.1% vs. 60.7%, p  = 0.015) or overweight/obese (25% vs. 69.2%, p  =  0.016) compared to women with lower pro-inflammatory cytokine values. Conclusion: We identified a pro-inflammatory burst at the third trimester, indicative of innate immune activation, in women with higher levels of both depressive and anxious symptoms, as well as differences in pro-inflammatory changes across time. We also found significant differences in cytokine levels by race, ethnicity, and overweight/obesity status. These results point the way toward future longitudinal work that considers race/ethnicity, timing, and weight status, and evaluates perinatal mood and anxiety disorders in the context of changing immune functioning across the peripartum.